EDITORIAL - Bianchi, Marcus V. A. (Revista de Engenharia Térmica, 2006)
The search for sustainable energy solutions has accelerated significantly in recent years driven by concerns caused by supply limitations, such as Peak Oil (or Gas, Coal, and Uranium), and by climate change. Many communities and industries are now facing the prospect of increased energy costs, potential energy supply disruptions, and carbon emission limits. Recently, the scientific academies of 13 countries1 (including Brazil) issued a joint statement calling on world leaders to increase energy efficiency, promote a shift to less-polluting energy sources, and intensify research into new energy technologies that produce no emissions. Also recently, a coalition of 16 of the world’s biggest cities (São Paulo is one of them), under a plan developed by the William J. Clinton Foundation2, pledged investments of billions of dollars to cut building energy use and releases of heat-trapping gases linked to global warming. The field of thermal sciences plays a critical role in managing these challenges. In a recent initiative, the National Science Foundation3 invited a number of thermal science researchers to identify frontier challenges and associated opportunities in five areas, one of which was sustainable energy technologies (the remaining were biological systems and biotechnology, security, information technology, and nanotechnology). While a final report was not yet published when this editorial was written, the passionate discussions pointed to action in research and education from academic institutions, government, and industry. Some of the topics discussed include fuel cells, seawater agriculture, biomass, sustainability metrics, carbon sequestration, and broad education of non-technical individuals on thermal sciences. The research findings published in Engenharia Térmica in the past have shown significant progress in areas related to energy, particularly oil and renewables. We are confident we will continue to receive articles’ submissions that help enable sustainable energy solutions in the near future.